Search 74,395 tutors
0 0

# 12x+9-4x-4=3x-7-X+30

I need help solving this equation. Thank You

Hi again Pj;
12x+9-4x-4=3x-7-x+30
Let's combine like terms on both sides...
(12x-4x)+(9-4)=(3x-x)+(-7+30)
8x+5=2x+23
Let's isolate x...
Let's subtract 5 from both sides...
-5+8x+5=2x+23-5
8x=2x+18
Let's subtract 2x from both sides...
-2x+8x=2x+18-2x
6x=18
Let's divide both sides by 6...
(6x)/6=18/6
x=3

Let's check our results in the original equation...
12x+9-4x-4=3x-7-x+30
Let's substitute x with 3...
[12(3)]+9-[4(3)]-4=[3(3)]-7-(3)+30
36+9-12-4=9-7-3+30
45-16=2+27
29=29
It works!

PJ,

This equation isn't too bad. Just a couple steps and I bet you'll recognize what to do quickly.

12x+9-4x-4 = 3x-7-x+30

Step 1) Combine like terms
*If I think of the equation as having a left side and a right side (split by the = sign), I'm going to combine the similar terms on the left and right.

LEFT: 12x+9-4x-4  ---->8x+5          (I did 12x-4x and 9-4)

RIGHT: 3x-7-x+30 -----> 2x+23       (3x-1x and -7+30)

So now we have 8x+5 = 2x+23   (The variable is on both sides of the = sign) (Not good)

Step 2) Eliminate one of the variables

8x+5 = 2x+23   (I'm going to subtract 2x from both sides to get rid of one variable
-2x      -2x

6x+5 = 23   (Now it's just a two-step equation, easy!)
-5     -5

6x=18  -----> x=3

**Don't forget to check!

12(3)+9-4(3)-4   =  3(3)-7-3+30

29 = 29 (Correct!)
To solve this equation, we need to combine all of constants and the x terms on each side of the equation:

12x + 9 - 4x - 4 = 3x - 7 - x + 30

8x + 5 = 2x + 23

Now, we subtract 5 from both sides and subtract 2x from both sides:

6x = 18

Now we divide both sides by 6

x = 18/6

x = 3